The Ubiquity of the Armadillo: An Imaginary Friend in Zerocalcare’s Transmedia Universe (Altre Modernità, 2025)
This essay aims to analyze the character of the Armadillo within the transmedia universe of the Roman cartoonist Michele Rech, known as Zerocalcare. Considering that characters play a fundamental role in contemporary “media culture” and their ubiquity often entails pronounced heterogeneity (Thon 176), examining the Armadillo in its various manifestations—a figure oscillating between an imaginary friend and the protagonist’s voice of conscience (Aletta 378)—is essential to understanding the work of the most widely read Italian cartoonist of the past fifteen years.In this essay, I propose to examine the character of the Armadillo in light of its characterization as an imaginary friend, a figure deeply rooted in the tradition of comic storytelling. To this end, supported by psychological research, the article investigates how comics have interpreted the phenomenon of imaginary friendship. Subsequently, through the lens of transmedia narratology, I will study the characterization of the Armadillo across different media platforms, including Zerocalcare’s blog, the volumes published by Bao, and the Netflix series, with particular attention to the interactions between the Armadillo, the protagonist, and other personifications of his conscience. Within Zerocalcare’s transmedia universe, the Armadillo revisits the traditional figure of the imaginary friend, reshaping and expanding it to serve multiple functions: from an instrument of autobiographical introspection to a generational allegory, from a narrative device to a diegetic connective element within the franchise.
Keywords: Zerocalcare; Armadillo; imaginary friend; transmedial characters; transmedial narratology